Disordered Toll‐like receptor 2 responses in the pathogenesis of pulmonary sarcoidosis. (6th August 2013) - Gabrilovich, M. I.; Walrath, J.; van, J.; Nethery, D.; Seifu, M.; Kern, J. A.; Harding, C. V.; Tuscano, L.; Lee, H.; Williams, S. D.; Mackay, W.; Tomashefski, J. F.; et al.
Summary In this study, we hypothesized that the granulomatous disorder sarcoidosis is not caused by a single pathogen, but rather results from abnormal responses of Toll‐like receptors (TLRs) to conserved bacterial elements. Unsorted bronchoalveolar lavage (BAL) cells from patients with suspected pulmonary sarcoidosis and healthy non‐smoking control subjects were stimulated with representative ligands of TLR‐2 (in both TLR‐2/1 and TLR‐2/6 heterodimers) and TLR‐4. Responses were determined by assessing resulting production of tumour necrosis factor (TNF)‐α and interleukin (IL)‐6. BAL cells from patients in whom sarcoidosis was confirmed displayed increased cytokine responses to the TLR‐2/1 ligand 19‐kDa lipoprotein of Mycobacterium tuberculosis (LpqH) and decreased responses to the TLR‐2/6 agonist fibroblast stimulating ligand‐1 (FSL)‐1. Subsequently, we evaluated the impact of TLR‐2 gene deletion in a recently described murine model of T helper type 1 (Th1)‐associated lung disease induced by heat‐killed Propionibacterium acnes. As quantified by blinded scoring of lung pathology, P. acnes‐induced granulomatous pulmonary inflammation was markedly attenuated in TLR‐2–/– mice compared to wild‐type C57BL/6 animals. The findings support a potential role for disordered TLR‐2 responses in the pathogenesis of pulmonary sarcoidosis.